विधागत अनुसन्धान स्वरूप औचित्य र महत्व Genre-Based Research Nature, Rationale, and Significance - Bhattarai, Badri Prasad (Educational Journal, 2026)
विधागत अनुसन्धानले विधासम्बन्धित अनुसन्धानको अवधारणा निर्माण गर्न सहयोग गरेको हुन्छ। विधागत अनुसन्धानले समस्या अनुरूप समाधानका निमित्त स्वरूप औचित्य र महत्वसँग अनुसन्धानलाई डो¥याइ रहेको हुन्छ । प्रत्येक विधागत अनुसन्धानका आफ्नै प्रकारका उपयोगिता र सीमा हुन्छन् । समस्याविशेषको समाधानका लागि स्वरूप औचित्य र महत्व गाँसिएका हुन्छन् । कविता, नाटक रंगमञ्च, उपन्यास, कथा, आत्मकथा, निबन्ध, कहानी जस्ता कुनै पनि विषयको अध्यनमा स्वरूप औचित्य र महत्व निर्धारण गरी मानवीय चेतनाका ग्रहण, विचार, भाव, सुख, दुःख र प्रेषणीयताका आधारबाट पूर्ण अध्ययन गर्न सकिन्छ । स्वरूप औचित्य र महत्वका आधारमा विधागत अध्ययन अघि वढाइने भएकाले जटिल मिश्रित विशिष्टिकृत समाजमा गरिने अध्ययन अनुसन्धानका विभिन्न समस्याहरू यसमा गाँसिएर आएका हुन्छन् । ती समस्याहरूको समाधानसँग जीवनको जटिलता र दुरूहतालाई समेत बौद्धिक आधार दिनु विधागत अनुसन्धानका आधार हुन् । साहित्यका कविता, नाटक रंगमञ्च, उपन्यास, कथा, आत्मकथा, निबन्ध, कहानीमा विधागत अनुसन्धान गर्दा विधागत स्वरूप औचित्य र महत्वले पार्ने प्रभावको समस्यासँग सम्बन्धित रही व्याख्यात्मक र विश्लेषणात्मक विधिबाट यो अनुसन्धान गरिएको छ । यस अनुसन्धानबाट स्वरूप औचित्य र महत्वमा आधारित भएर विधागत अनुसन्धान गर्दा अध्ययनले पूर्णता पाउने र विधासम्बन्धित अनुसन्धानको अवधारणा निर्माण गर्न पनि उपयोगी र सहयोगी हुने नतिजा प्राप्त हुन आएको छ । Genre-based research helps in developing the conceptual framework of research related to literary genres. It guides the research process by emphasizing the nature, rationale, and significance of inquiry in relation to the problem under investigation. Each genre-based research approach has its own utility and limitations. The nature, rationale, and significance of a study are closely connected to the solution of a particular problem. In the study of literary forms such as poetry, drama and theatre, novels, short stories, autobiographies, essays, and narratives, it is possible to conduct a comprehensive analysis by determining their nature, rationale, and significance and by examining human consciousness, perceptions, thoughts, emotions, joys, sorrows, and communicative functions. Since genre-based studies proceed on the basis of nature, rationale, and significance, they encompass various research problems that emerge within a complex, mixed, and specialized society. Providing an intellectual foundation for understanding and resolving these problems, as well as addressing the complexities and challenges of life, constitutes the basis of genre-based research. This study has been conducted using explanatory and analytical methods to examine the influence of genre-specific nature, rationale, and significance in literary research involving poetry, drama and theatre, novels, stories, autobiographies, essays, and narratives.The findings indicate that genre-based research grounded in nature, rationale, and significance enables a more comprehensive understanding of the subject matter. Furthermore, it proves useful and supportive in constructing the conceptual framework of genre-related research.